Audit of peripheral neuromuscular stimulators at the hospitals staffed by the department of anaesthesia and perioperative medicine at the University of Cape Town - Joubert, Andries Thomas (Department of Anaesthesia and Perioperative Medicine, 2020)
Rationale: Inadequate monitoring of neuromuscular blockade (NMB) may result in worse patient outcomes, therefore NMB monitor availability is a minimum requirement for perioperative care according to the South African Society of Anaesthesiologists’ (SASA) 2018 Practice Guidelines. The authors performed an audit of peripheral nerve stimulators (PNS) functionality and availability at their institution. In the researcher’s experience the peripheral nerve stimulators (PNS) in use at his institution are not always easily available and some units malfunction at times. There are also not many units that can give a graphical display of a train of four ratio. This observation spurred the idea to do an audit on neuromuscular monitoring at this institution, by focusing on the availability and functionality of peripheral nerve stimulators. Methods: After ethics approval was obtained, an audit was performed. In order to assess function, the PNS were attached to an electrical circuit with a skin equivalent resistance. The resultant current impulses generated using Train-of-Four (TOF) mode and Double Burst Stimulation modes (DBS) were recorded with a voltage scope meter and visually assessed that the TOF was present and appeared equal. PNS availability was assessed in theatre and recovery areas against the SASA guideline standard of nerve stimulator availability. Results: Of the 65 PNS units assessed, 39 units were deemed to be dysfunctional and 26 units fully functional. The most frequent fault found (30 units) related to faulty or absent PNS electrode cables. Eight functional PNS units with TOF ratio display capability were found. The working PNS showed good inter-device peak voltage measurement correlation. Of the 59 areas identified where PNS should be easily available, only 37 areas met the PNS availability criteria suggested in the SASA guidelines. Discussion: This audit revealed that overall there were not enough functional PNS available at the institution, when measured against the SASA standard. The clinical significance of these findings would vary depending on the actual usage rate of NMBs in the area concerned. The logistics of tracking aPNS unit’slocationalso turnsoutto be paramountinsituationswherenerve stimulators have to be shared between areas. From a technical point of view, the working PNS were found to be very consistent in their delivered voltage bursts. Future use of the first generation PNS (without TOF ratio display) will continue to decline, because of their inability to monitor neuromuscular function bymodern standards, and the poor availability ofreplacement parts for models no longer manufactured. The cost and availability of repairs and cable replacementsshould be factored into the decision when acquiring more PNS units. Conclusion: This audit highlighted the need for more new generation PNS with TOF-ratiodisplay- ability to align the institution with the recommendations from SASA standards and the anaesthetic literature. It also highlighted the accuracy and consistency of delivered current bursts by the working PNS devices.